Pengaruh Tone Dalam Laporan Tahunan Dan Ownership Structure Terhadap Nilai Perusahaan - Kennard Robby Yulianto; Aristofer Austin; Saarce Elsye Hatane; Oviliani Yenty Yuliana (Business Accounting Review, 2020)
This study aims to determine the effect of tone in the company's annual report and company ownership structure on firm value (tobin's Q) in the tourism and hospitality sector. This study also uses the current ratio, debt to equity ratio, return on assets and firm size as control variables. The samples used in this study were 92 tourism and hospitality sector companies listed on the Indonesia Stock Exchange (IDX), Stock Exchange of Thailand (SET), Malaysia Stock Exchange (MYX), Singapore Stock Exchange (SGX), and Philippine Stock Exchange (PSE) in 2015-2018. In this study, tone disclosure is measured by analyzing sentiment in the textual narrative section of the company's annual report using NVIVO. Meanwhile, ownership structure is measured by dividing the percentage of managerial and institutional share ownership by the number of outstanding shares. The data analysis technique used in this research is panel data regression analysis using Gnu Regression, Econometrics and Time-series Library (GRETL) software. The results showed that the tone concluded with the net tone (the difference between positive and negative tones) had a positive and significant effect on firm value. Meanwhile, managerial ownership has a significant positive effect on firm value and institutional ownership has a significant negative effect on firm value.